HASIL BELAJAR IPS TERPADU MENGGUNAKAN NHT DAN LT DENGAN MEMPERHATIKAN MOTIVASI BERPRESTASI - Ahmad Jaenudin; Pujiati Pujiati; Nurdin Nurdin (FKIP Unila, 2015)
This research assess about learning outcomes of integrated social class by using NHT and LT model considering the motivation of achievement. Data collection is through observation, interview, documentation and tests. Hypothesis testing is using two independent samples t-test and two ways anava. The research results: (1) there were differences in learning outcomes of integrated social class between students who use the model of learning cooperative NHT type compared to LT type, (2) the average learning outcomes of integrated social class on the students who are taught by using NHT model is higher than by using LT model on the students who have low motivation achievement, (3) the average learning outcomes of integrated social class on the students who are taught with NHT is lower than LT on the students who have high motivation achievement, and (4) there are interactions between cooperative learning model with the motivation of achievement on the subjects of integrated social class.Penelitian ini mengkaji tentang hasil belajar IPS Terpadu dengan menggunakan model NHT dan LT dengan memperhatikan motivasi berprestasi. Pengumpulan data melalui observasi, wawancara, dokumentasi dan tes. Pengujian hipotesis menggunakan t-test dua sampel independen dan anava dua jalan. Hasil penelitian (1) Terdapat perbedaan hasil belajar IPS Terpadu antara siswa yang menggunakan model pembelajaran kooperatif tipe NHT dibandingkan dengan tipe LT, (2) Rata-rata hasil belajar IPS Terpadu pada siswa yang diajar dengan menggunakan model NHT lebih tinggi dibandingkan dengan LT pada siswa yang memiliki motivasi berprestasi rendah, (3) Rata-rata hasil belajar IPS Terpadu pada siswa yang diajar dengan menggunakan model NHT lebih rendah dibandingkan dengan LT pada siswa yang memiliki motivasi berprestasi tinggi, dan (4) Ada interaksi antara model pembelajaran kooperatif dengan motivasi berprestasi pada mata pelajaran IPS Terpadu.Kata kunci: hasil belajar, LT, NHT